login
a(n) = a(n-1)^3 + a(n-2)^3 - (a(n-1) - a(n-2))^3, a(1) = a(2) = 1.
0

%I #15 Mar 25 2013 12:45:56

%S 1,1,2,8,304,2160640,4256950094225408,

%T 117462917657284681348398871061442068480

%N a(n) = a(n-1)^3 + a(n-2)^3 - (a(n-1) - a(n-2))^3, a(1) = a(2) = 1.

%C a(9) has 93 digits and thus is too long to be added. - _Giovanni Resta_, Mar 22 2013

%e a(3) = (1)^3 + (1)^3 - (1-1)^3 = 2.

%e a(4) = (2)^3 + (1)^3 - (2 - 1)^3 = 8.

%e a(5) = (8)^3 + (2)^3 - (8 - 2)^3 = 512 + 8 - 216 = 304.

%K nonn

%O 1,3

%A _Gregory Gabovich_, Mar 21 2013

%E a(8) from _Giovanni Resta_, Mar 22 2013